The Gender Paradigm and Custody Disputes - Dutton, Donald G. (International Journal for Family Research and Policy, 2015)
In 2008, two important sources of information were made available to professionals engaged in child custody assessments. One was the website of the American Bar Association that listed ten "myths" about domestic violence and set the record straight (or so it claimed) by citing empirical studies. The other was the Wingspread Conference on Domestic Violence and Family Courts held in Wisconsin in 2007, which issued the Wingspread Report published in 2008 in a special issue of the Family Court Review on child custody. Both of these important sources used the gender paradigm as their heuristic for family violence. In this paper, I show how empirical support for the gender paradigm does not exist. To the contrary, many large scale studies of domestic violence contradict the gender paradigm and show very different patterns of intimate partner violence (IPV). Assessment in custody disputes has to be recalibrated to eliminate this source of generic bias against males and to allow family courts to operate fairly.